Analisis Kandungan Total Lemak pada Food Replacement (X) dan Fermentasi Akar Teratai (Nelumbo nucifera) - Cut Rahil Sofia; Roy Indrianto Bangar; Erida Novriani (Yayasan Literasi Sains Indonesia, 2026)
This research relies on the analysis of fat content from the food replacement product (x) and lotus root (nelumbo nucifera) fermentation by utilizing the Soxhlet method. The experiment was conducted by extraction using n-hexane solvent for six hours. The fat content was determined based on the difference in weight after extraction. The findings showed that the fat content in the food replacement product (x) reached 63.60%, while in the lotus root fermentation it was 89.19%. These high numbers are influenced by the composition of the ingredients used, the effectiveness of nonpolar solvents, as well as changes in the matrix structure due to fermentation which increases lipid accessibility. The fermentation process, which lasted for 22 days, enhances enzymatic effectiveness that damages cell walls, thereby facilitating the extraction of lipophilic compounds. The results of this study indicate that fermentation can increase the measurement of fat in plant-based food materials, but the figures obtained reflect the fat that was successfully extracted, not pure fat. According to regulations in Indonesia, there is not yet a maximum limit for fat content in foods for special nutritional needs.